Macromolecular Synthesis During Microcycle Sporogenesis of Bacillus cereus T - MacKechnie, Ian (1970)
Microcycle sporogenesis induced in Bacillus cereus T by phosphate limitation occurs over a narrow range of phosphate to spore inoculum ratios. Sufficient phosphate is required to satisfy the demands for a twofold increase in deoxyribonucleic acid; net ribonucleic acid synthesis is not required. The total ribonucleic acid content of the culture was variable, and deoxyribonucleic acid synthesis was restricted to a twofold increase. Developmental changes during outgrowth occurred synchronously, whereas enzyme synthesis was periodic. The timing of the synthesis of tricarboxylic cycle enzymes, extracellular protease, arginase, histidase, and alkaline phosphatase was measured. Histidase could be induced after 2.5 hr throughout microcycle sporogenesis. Several other features of macromolecular synthesis during microcycle sporogenesis are described. Differences between this pattern and those observed during outgrowth leading to cell division are discussed. A technique for accurately estimating the levels and time of synthesis of incompletely extractable, labile enzymes is also presented.